Joint Russian-Mongolian Statement - Ivanov, Igor; Erdenechuluun, Luvsangiin (Mongolian Journal of International Affairs, 2013)
DOI: http://dx.doi.org/10.5564/mjia.v0i12.100 Mongolian Journal of International Affairs No.12 2005: 107-111